Agricultural Information's Impact on the Adaptive Capacity of Ghana's Smallholder Cocoa Farmers - Maguire-Rajpaul, Victoria A.; Khatun, Kaysara; Hirons, Mark A. (Frontiers in Sustainable Food Systems, 2020)
Ghanaian smallholders grow one quarter of the world's cocoa, but climate change, individual extreme weather events, such as droughts, as well as deforestation increasingly threaten cocoa production. Pertinent information could bolster adaptive capacity. However, in Ghana's cocoa sector, relevant agricultural information is not available to all farmers, which can exacerbate power asymmetries. This paper focuses on how (i) agricultural and drought-adaptive information and (ii) socio-economic characteristics shape a cocoa farmer's adaptive capacity. We conducted our study in the aftermath of 2015–16's prolonged El Niño-induced drought that negatively impacted the livelihoods of cocoa smallholders across Ghana. In 48 semi-structured interviews and 12 focus groups, we asked smallholders how they responded to the drought to decipher how adaptive capacity compares between farmers receiving four different sources of agricultural information, and of diverse socio-economic status. Overall, agricultural information improved cocoa farmers' adaptive capacity compared to those who received no formal agricultural information. Smallholders detailed adaptive techniques that would be accessible to, and thus replicable by, other poorly-resourced cocoa farmers. Shade tree management and income diversification were identified as pertinent adaptive actions. However, we identified a divergence between exposure to agricultural information and its transformation into substantive adaptive action. Additionally, informal information sharing between smallholders represents an underutilized resource by extension programmes. We found that adaptive capacity is also determined by socio-economic characteristics: particularly gender, and to a lesser extent formal education level, proximity to asphalt roads, and land tenure. Finally, we present evidence that framing adaptive techniques in relatable terms that resonate with farmers' immediate livelihood concerns could narrow the adaptation deficit prevalent in Ghana's cocoa sector.